2021
DOI: 10.1101/2021.10.11.463921
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Catestatin selects for the colonization of antimicrobial-resistant gut bacterial communities

Abstract: The gut microbiota is in continuous interaction with the innermost layer of the gut, namely the epithelium. Among the various functions of the gut epithelium, is to keep the microbes at bay to avoid overstimulation of the underlying mucosa immune cells. To do so, the gut epithelia secrete a variety of antimicrobial peptides, such as catestatin (CST). As a defense mechanism, gut microbes have evolved antimicrobial resistance mechanisms to counteract the killing effect of the secreted peptides. To this end, we t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
14
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 69 publications
6
14
0
Order By: Relevance
“…Speci cally, butyrate was signi cantly lower in the donor CST-KO mice compared to their WT counterparts as reported previously (Fig. 1F) (González-Dávila et al, 2021). Levels of acetate and butyrate increased signi cantly in CST-KO FMT−WT compared to CST-KO (Fig.…”
supporting
confidence: 86%
“…Speci cally, butyrate was signi cantly lower in the donor CST-KO mice compared to their WT counterparts as reported previously (Fig. 1F) (González-Dávila et al, 2021). Levels of acetate and butyrate increased signi cantly in CST-KO FMT−WT compared to CST-KO (Fig.…”
supporting
confidence: 86%
“…Recently, we and others have shown that CST-KO mice display altered gut microbiota composition compared to their wild-type counterparts (González-Dávila et al, 2021; Muntjewerff, Lutter, et al, 2021). In particular, CST treatment reduced the abundance of Staphylococcus and Turicibacter in CST-KO and WT mice, while Alistipes , Akkermansia , and Roseburia were significantly increased in the CST-KO group (González-Dávila et al, 2021).…”
Section: Introductionmentioning
confidence: 93%
“…The copyright holder for this preprint this version posted February 24, 2022. ; https://doi.org/10.1101/2022.02.24.481402 doi: bioRxiv preprint in CST-KO and WT mice, while Alistipes, Akkermansia, and Roseburia were significantly increased in the CST-KO group (González-Dávila et al, 2021).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations